Choose your wow! a disciplined agile approach to optimizing your way of working - Ambler, Scott W. 1966-; Lines, Mark 1964- (Project Management Institute, Inc., 2022)
"Hundreds of organizations around the world have already benefited from Disciplined Agile Delivery (DAD). Disciplined Agile® (DA) is the only comprehensive tool kit available for guidance on building high-performance agile teams and optimizing your way of working (WoW). As a hybrid of the leading agile, lean, and traditional approaches, DA provides hundreds of strategies to help you make better decisions within your agile teams, balancing self-organization with the realities and constraints of your unique enterprise context"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Agile software development; Project management; Teams in the workplace; Méthodes agiles (Développement de logiciels); Gestion de projet; Équipes de travail